EDUKASI PENATALAKSANAAN GANGGUAN JIWA DENGAN PERILAKU KEKERASAN DI POSYANDU JIWA KELURAHAN BALOWERTI - Yunarsih; Heny K; Sucipto; Puguh; Nuritanilasari (Indonesian Health Literacy Journal, 2025)
Mental disorders with violent behavior are serious issues requiring comprehensive and continuous management at the community level. This community service activity aimed to improve the knowledge and skills of mental health cadres and companions at the Balowerti Mental Health Post (Posyandu Jiwa) in managing patients with violent behavior. The method was implemented through health education using lectures, interactive discussions, and simulations of handling violent behavior in mental disorder patients. The results showed increased participants’ understanding of signs of violent behavior, preventive measures, and appropriate referral procedures. Participants also demonstrated improved empathy and therapeutic communication skills. This activity proved effective in strengthening the capacity of cadres and companions to support individuals with mental disorders in the community.